Modeling of wind turbine based on dual DFIG generators - Rabiaa Mahroug; Mohamed Matallah; Salam Abudura (Institute of Advanced Engineering and Science, 2022)
In order to investigate a viable approach to fully exploit the wind speed, the present work investigates the application of a novel wind turbine consisting of dual doubly-fed induction generators (DFIG). The model can be further used to apply in areas where the winds are high to achieve high conversion efficiency in order to produce large electric power and increase the wind turbine capacity with an economy of hardware on the one hand, and to reduce the installation cost on the other. Furthermore, this model is always guarantees the continuity of power production because if one generator fails, the second generator will keep working until the broken one is repaired. The proposed model of the wind turbine based on dual doubly-fed induction generators (WT-dual-DFIG) were using the indirect field-oriented control (IFOC) was validated by wind turbine based on single doubly-fed induction generator (WT-single-DFIG) in MATLAB/Simulink. The results of simulation show that the simulated responses of the WT-dual-DFIG increased the power by a factor of about 14.3% compared to a WT-single-DFIG due to the use of a variable speed dual-DFIG. Finally, we can say that the WT-dual-DFIG model is strongly developed and could be applied in the coming years.